Domains of faith impact: how "faith" is perceived to shape faith-based international development organisations. Issue 3 (2nd April 2016) - Ware, Vicki-Ann; Ware, Anthony; Clarke, Matthew
ABSTRACT: Increasing interest in faith-based international development organisations (FBOs) recently has improved understanding of these agencies. One reason for complex, often contradictory findings is the lack of frameworks analysing the interactions of worldviews on organisational structures, processes, and behaviours of agencies, and development outcomes. We utilise Lincoln's (2003. Holy Terrors: Thinking about Religion after September 11 . Chicago: University of Chicago Press) four "domains of religion" to explore how the literature reports faith impacting the shape of development FBOs' structures, behaviours, and outcomes. Literature suggests faith has a significant impact upon these agencies. We outline very specific similarities and differences, highlighting the importance of nuanced analysis of faith's role in FBOs. Further research is needed to build more evidence around these impacts of faith on FBOs.